Plant growth and development of Ruellia brittoniana Leonard affected by indole-3-butyric acid and daminozide - Mustaffer, Nurhazwani (2017)
Ruellia brittoniana is a landscape plant, generally propagated by seeds and cuttings but the problem lies in a very low germination percentage. Propagation using stem cutting is therefore become a logical choice but the success of the propagation could be low without rooting hormone and it may vary amongst different type of cuttings. It is a fast growing plant with a strong tendency of vegetative growth that occurs at the expense of flowering capability, thus regular pruning for height control is necessary. Chemical pruning using suitable growth retardant may offer similar effects on stem and branch elongation, and flowering of the plants could be promoted. This study was carried out to determine the rooting performance of various type of cutting materials by using different concentration of indole 3-butyric acid (IBA) and to evaluate the varying rate of daminozide on the growth and flowering of Ruellia brittoniana. Evaluation of the effects of different IBA concentrations revealed that stem cuttings dipped in IBA at 500 mg/L produced significantly higher root formation, and generated plants with larger leaf and root area compared to the non-treated cuttings and those treated with 250 and 1000 mg/L IBA. Overall, hardwood cutting produced the highest root formation, root and leaf area. On the whole plant, foliar application of daminozide effectively reduced the vegetative growth, as seen in reduction of plant height, internode length, leaf area, dry weight of leaves, stem and roots. Daminozide concentration range between 1000 mg/L and 2000 mg/L had reduced the plant height by 49-58% compared to control with less reduction in number of flowers compared to plants treated with higher daminozide concentration. Variation in application frequency of daminozide markedly affected the growth and physiological processes of the plants. Results of a two factorial experiment involving two application frequencies (double and triple applications) and five concentrations of daminozide (0, 500, 1000, 1500, 2000 mg/L) showed that different concentration of daminozide and application frequencies significantly affected the vegetative growth, photosynthesis, transpiration and chlorophyll content. Daminozide at 500 mg/L with triple application caused a reduction of 42% in plant height compared to those in control with less detrimental effects on flower number. Daminozide application had no effect on stomatal conductance and leaf nutrients composition. In conclusion, hardwood cutting treated with 500 mg/L of IBA was the best combination for Ruellia brittoniana rooting and application of daminozide at 500 mg/L given in triple application was found to be effective in producing short, compact plants with more flowers.